Distinct Cell-specific Roles of NOX2 and MyD88 in Epileptogenesis - Almeida, Cayo; Pongilio, Renan Paschoalino; Móvio, Marília Inês; Higa, Guilherme Shigueto Vilar; Resende, Rodrigo Ribeiro; Jiang, Jianxiong; Kinjo, Erika Reime; Kihara, Alexandre Hiroaki (Frontiers in Cell and Developmental Biology, 2022)
It is well established that temporal lobe epilepsy (TLE) is often related to oxidative stress and neuroinflammation. Both processes subserve alterations observed in epileptogenesis and ultimately involve distinct classes of cells, including astrocytes, microglia, and specific neural subtypes. For this reason, molecules associated with oxidative stress response and neuroinflammation have been proposed as potential targets for therapeutic strategies. However, these molecules can participate in distinct intracellular pathways depending on the cell type. To illustrate this, we reviewed the potential role of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (NOX2) and myeloid differentiation primary response 88 (MyD88) in astrocytes, microglia, and neurons in epileptogenesis. Furthermore, we presented approaches to study genes in different cells, employing single-cell RNA-sequencing (scRNAseq) transcriptomic analyses, transgenic technologies and viral serotypes carrying vectors with specific promoters. We discussed the importance of identifying particular roles of molecules depending on the cell type, endowing more effective therapeutic strategies to treat TLE.